(untitled) - Callahan, Kevin R. (Hoboken, NJ, 2004)
The authors, both consultants and management educators in private practice, give an overview of strategic planning in business. They describe types of organizations and their problems with other methods of project management, the basics of strategic planning and its focus on implementing the right projects. They continue with the planning process and its interconnected system of goals and indicators, initiation, execution, communication, and control, and the special considerations of the mature project. They also address the current reality of managing a portfolio of projects that may or may not be interconnected. The text includes a web site with forms and templates
Keywords: Project management